2022
DOI: 10.1080/08039488.2022.2032330
|View full text |Cite
|
Sign up to set email alerts
|

Driving risks of young drivers with symptoms of attention deficit hyperactivity disorder: association with the dopamine transporter gene VNTR polymorphism

Abstract: BackgroundRoad traffic injuries are a leading cause of death for young adults, and young drivers with higher expression of symptoms of attention deficit-hyperactivity disorder (ADHD) could pose an even greater risk in traffic. Dopaminergic dysfunction has been found to occur in ADHD, with the dopamine transporter (DAT) gene VNTR polymorphism (DAT1 VNTR; rs28363170) being one of the most consistent genetic markers. Thus, we aimed at clarifying how the ADHD symptoms and the DAT1 VNTR relate to risk-taking behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
3
1
Order By: Relevance
“…Finally, unlike other studies, we failed to find an association between gender, substance abuse or ADHD and risk of recidivism. Whereas in a recent study, drivers who reported more ADHD symptoms also reported greater traffic risk-taking [ 41 ], we found no association in our study between probable ADHD and recidivism ( p = 0.55 for the intervention group and p = 0.25 for the control group). Similarly, numerous studies have shown an association between alcohol and/or cannabis consumption and risk of accident [ 42 , 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, unlike other studies, we failed to find an association between gender, substance abuse or ADHD and risk of recidivism. Whereas in a recent study, drivers who reported more ADHD symptoms also reported greater traffic risk-taking [ 41 ], we found no association in our study between probable ADHD and recidivism ( p = 0.55 for the intervention group and p = 0.25 for the control group). Similarly, numerous studies have shown an association between alcohol and/or cannabis consumption and risk of accident [ 42 , 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The epigenetic regulation of DAT1 gene promoter region was also investigated in relation to excessive use of the Internet in school-age youths and pre-adolescents 16 as well as in youths (from 18 to 34 years) 17 . Of note, the human DAT1 gene is also characterized by a polymorphic 40-base pair (bp) variable number of tandem repeats (VNTR) in the 3’-untranslated region (3’-UTR), previously associated with impulsivity and drug dependence/addiction 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is no association between VNTR polymorphism of DAT1 and DRD4 genes and ADHD among Indonesian children based on case-control study ( Thursina et al, 2020 ). DAT1 9 R carriers have a higher likelihood of high traffic risk behavior in case only they also have ADHD symptoms ( Tokko et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is no available standardized protocol for the auxiliary examinations which can assist in diagnosis despite the presence of many studies. Moreover, ADHD is frequently comorbid with other conditions in about 75% of the cases ( Pliszka, 1998 ; Fayyad et al, 2007 ), including anxiety disorders, oppositional defiant disorder, mood disorders, substance use disorders, and conduct disorders ( Rizzo et al, 2010 ; Nogueira et al, 2014 ; Tokko et al, 2022 ). All the aforementioned issues make this disorder more complex ( Dias et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%